2017
DOI: 10.1016/j.aprim.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de los cuidados y los conocimientos parentales sobre la fiebre en la infancia

Abstract: A correct care of fever is observed despite the low knowledge. A good strategy to promote a correct care of febrile child is to do sanitary education with update information and adapted it to parents, focusing on the differences between ethnic groups because they seem to have inaccurate beliefs about fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
(35 reference statements)
2
4
0
2
Order By: Relevance
“…The lack of evidence for the studied associations may be due to the small sample size for such analysis. In relation to knowledge about fever management, one-third of survey respondents considered fever values that were below the definition of fever, similar to what has been described by other authors, 3,21 and this may predispose to an inadequate antipyretic agent use and an overburden on the health care system. Among thermometer use, the digital type prevailed, as observed in other populations.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The lack of evidence for the studied associations may be due to the small sample size for such analysis. In relation to knowledge about fever management, one-third of survey respondents considered fever values that were below the definition of fever, similar to what has been described by other authors, 3,21 and this may predispose to an inadequate antipyretic agent use and an overburden on the health care system. Among thermometer use, the digital type prevailed, as observed in other populations.…”
Section: Discussionsupporting
confidence: 62%
“…Among thermometer use, the digital type prevailed, as observed in other populations. 3,6,16,22 It is worth noting that part of our sample used a mercury thermometer, and that there were differences compared to other studies, which showed a greater 3 or smaller use. 19 The preferred site to measure body temperature was the armpit in most cases, which is consistent with current recommendations.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations